Stem cell treatment for the spinal cord injury – A concise review - Ponemone, Venkatesh; Choudhury, Khushboo; Harris, Kenneth Lee; Dewan, Yashbir (Indian Journal of Neurotrauma, 2014)
A spinal cord injury (SCI) is any injury of the spinal cord caused due to trauma and mostly comprise of damage to the nerves associated with the spinal cord and they can be classified as being complete or incomplete. Spinal cord injuries account for a majority of lower body disabilities due to accidents and trauma. Cell transplantation, as a therapeutic intervention for spinal cord injury (SCI), has been extensively studied by scientists and researchers in recent years using stem cell that has shown considerable promise in treating patients with SCI and thus restores lost functions by replacing lost or damaged cell populations. Spinal cord injuries account for a majority of lower body disabilities due to accidents and trauma. SCI also paves way for a lot of other disabilities associated with blood vessels as well and bone deformities. The global burden of SCI, economically, runs into millions as complete cure is not possible. The number of clinical trials that have been conducted for phase 1 studies of spinal cord injury is a staggering number and currently 246 trials are being conducted in their initial phases. However, many questions remain unanswered and more continue to emerge. This review will comprehensively cover publications in the field from the last years and examine the biological effects of SCI.
Keywords: Spinal cord injury; Stem cells; Bone marrow; Bone marrow derived stem cells; Mesenchymal stem cells